2016
DOI: 10.1007/s11240-016-1016-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture type and elicitation affects secoiridoid and xanthone LC–ESI–TOF MS profile and production in Centaurium erythraea

Abstract: Centaurium erythraea is medicinal plant with high content of secoiridoid glycosides and xanthones with gastroprotective, hepatoprotective and antioxidative properties. In vitro culture based C. erythraea production would offer sustainable and economically feasible alternative to wild plant harvest provided that comparable productivity could be achieved in artificially propagated plants. To identify most productive C. erythraea system the secoiridoid glycoside and xanthone production and profiles using liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Likewise, in other genera of Gentianaceae family, Krstic et al [35] described the higher production of xanthones and secoiridoids in organ cultures. Boroduske et al [36] advocated shoot culture more suitable for secoiridoid production.…”
Section: Effect Of Pgr On Organogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in other genera of Gentianaceae family, Krstic et al [35] described the higher production of xanthones and secoiridoids in organ cultures. Boroduske et al [36] advocated shoot culture more suitable for secoiridoid production.…”
Section: Effect Of Pgr On Organogenesismentioning
confidence: 99%
“…Transcriptome studies revealed the elevated gene expressions involved in the metabolic pathways of secoiridoid and xanthone compounds. Research indicates that chitosan shows considerable increase of swertiamarin compound in Centaurium erythraea [36], amarogentin compound in Swertia chirata [12] and mangiferin compound in Hypericum perforatum cultured plants [42]. Chitosan is well known to release various defense genes and also to induce production of secondary metabolites in order to inhibit the growth of microbes [21,43].…”
Section: Elicitor Treatmentmentioning
confidence: 99%
“…Its gastroprotective [5], hepatoprotective, diuretic effects and hypoglycemic activity [6] and other medical activities have been described before [7]. The main representatives secoiridoid glycosides in Centaury herb are swertiamarin, gentiopicroside andsweroside [8,9] (Fig. 1).…”
Section: Introductionmentioning
confidence: 90%
“…Analysis was performed essentially as described in Ref. [12]. LC/MS data preprocessing was performed with MZmine 2.27 [13].…”
Section: Methodsmentioning
confidence: 99%